Das Problem der kulturellen Kontakte zwischen der Neuen und der Alten Welt in vorcolumbischer Zeit im Lichte der Pflanzengeographie - Groß, Hugo (ERDKUNDE, 1956)
The similarity of cultural elements which exists between the American Indians and Oceania, as well as the pre-Columbian civilisations of America and those of Egypt and the Near and Middle East, have repeatedly been explained by the assumption of cultural contacts between the Old and the New World in pre-Columbian and pre-Magellan times. This was done especially by ethnologists and anthropologists, but also by prehistorians and geographers, despite the established fact that the New World was settled by man via north-east Asia as late as the late Pleistocene period. Same diffusionists assume trans-Atlantic, but most of them trans-Pacific transfer of cultural elements in both directions. If noteworthy contacts did exist, they would have been bound 3. Big Bit of Old Poland Lives in Customs Here, Thc Milwaukee Journal, October 9, 1947. 4. Borun, Thaddeus: We, the Milwaukee Poles, Nowiny Publishing Company, Milwaukee 1946. 5. Bruce, William George: A Short History of Milwaukee, Bruce Publishing Company, Milwaukee 1936. 6. Census Tract Statistics, Chapter 32, United States Census of Population: 1950, Vol. III, U. S. Bureau of the Census, U. S. Government Printing Office, Washington, D. C., 1952. 7. City Regaining German Tide, The Milwaukee Journal, March 19, 1930. 8. East Side Polish Colony is Scattering Fast Today, The Milwaukee Journal, January 29, 1939. 9. Foreign Born Here Decrease, The Milwaukee Journal, February 6, 1923. 10. Gilbert, Patricia E.: Milwaukee Once Known As Athens of America, The Milwaukee Journal, April 22, 1939. 11. Gilbert, Patricia E.: Play Leading Roles in Industry, Politics and Business of City, The Milwaukee Journal, May 19, 1939. 12. Kerstein, Edward: Polish Pioneers, Lovers of Freedom, Laid Firm Foundation, The Milwaukee Journal, February 9, 1941. 13. McMahon, Paul: Customs of Old World Still Alivc in Milwaukee, The Milwaukee Journal, October 5, 1947. 14. Milwaukee German Settlers, The Milwaukee Journal, October 7, 1938. 15. Nativity and Parentage of the Foreign, White Stock, United States Census of Population: 1950, Series PC-14, No. 20, U. S. Bureau of the Census, U. S. Government Printing Office, Washington, D. C., 1954. 16. Sixth Street Has Distinction Claim, The Milwaukee Sentinel, January 8, 1922. 17. Stability of Milwaukee Attributed to Unrest in Germany Decades Ago, The Chicago Daily Tribune, June 24, 1930. 18. Still, Bayrd: Milwaukee: the History of a City, The State Historical Society, Madison 1948. to leave their mark in domestic animals, cultivated plants and weeds. By studying the oldest possible herbaria, manuscripts, reports about the flora and general reports of travels, the botanist, E. D. Merri!!, came however to the conclusion that, out of about 1500 cultigens of the world which existed at the time prior to Columbus and Magellan, only three species were common to both hemispheres, namely the sweet potato, the coconut, and the common gourd, and that the distribution of the cultigens (with the exception of the three mentioned above) which today are common to both the Old and the New World, is the result of shipping communications during the last 450 years. Thus the botanical data point against notable cultural contacts between the two hemispheres prior to this time. Consequently one has to conclude that the prehistoric civilisations of America must on the whole have developed independently.